Usability Analysis of Online Travel Agent Applications Using System Usability Scale and Electroencephalography - Larasati, Ayunda; Tranggono, Tranggono (Politeknik Negeri Batam, 2025)
In the digital era, technology has transformed the travel and tourism industry, with Online Travel Agents (OTAs) like Traveloka, Tiket.com, and Agoda offering convenient trip planning through digital platforms. Despite their popularity, issues such as navigation difficulties and unclear information still affect user satisfaction. This study aims to evaluate the usability of OTA applications using the System Usability Scale (SUS) based on the ISO 9241-11 standard and Electroencephalography (EEG) to analyze user physiological responses. The test involved 10 respondents and 4 task scenarios. The results showed that Traveloka achieved a SUS score of 85, with 95% effectiveness and 0.023 goals per second efficiency. Tiket.com scored 79 with 92.5% effectiveness and 0.026 goals per second efficiency, while Agoda scored 70 with 87.5% effectiveness and 0.016 goals per second efficiency. EEG data revealed that Traveloka and Tiket.com had the highest average alpha wave values, indicating respondents felt nervous or anxious, whereas Agoda showed higher beta wave values, suggesting respondents were calm and aware without full concentration. This study highlights that the usability of OTA applications is influenced by user experience, which can be measured subjectively through SUS and more deeply using EEG data to understand physiological responses when interacting with the application.